First report of raspberry bushy dwarf virus infecting raspberry in Argentina - Dal Zotto, Angelica; Cardozo, Andrea; Cabrera Mederos, Dariel; Nome Docampo, Claudia; Giolitti, Fabian; Cobelo, Claudia Monica (Dipartimento di Scienze del Suolo, della Pianta e degli Alimenti, Università di Bari, 2021)
In 2014-2015, raspberry (Rubus idaeus) cv. Autum bliss plants with dwarfism and foliar chlorosis were observed in commercial fields in parallel 42° in the Patagonia region of Argentina. Symptoms were similar to those observed in raspberry infected by Raspberry bushy dwarf virus (RBDV) in the USA (Ellis et al., 2005; Martin et al., 2013). A survey was conducted to determine if RBDV was also present in Argentinian raspberry fields. Transmission electron microscope observations of leaf dip preparations revealed the presence of spherical particles of 30 nm, resembling those of virus members of the genus Ideaovirus. RBDV was detected in 88 of the 130 plants (68%) tested using double-antibody sandwich ELISA with a specific polyclonal antiserum (Bioreba AG, Switzerland). RNA was extracted with Spectrum™ Plant Total RNA Kit (Sigma-Aldrich, USA) and tested by RT-PCR using a pair of specific primers to the capsid protein gene (Wang et al., 2008). Expected fragments of 825 bp were obtained and custom-sequenced in both directions (Macrogen, Korea). Nucleotide BLAST analysis of the complete sequence obtained (GenBank accession No. KY308191) showed 97% identity at the nucleotide level with virus isolates from Slovenia, Belarus, Switzerland and Japan (EU796088, FR687356, FR687358, AB948216, respectively). To our knowledge, this is the first report of RBDV infecting raspberry in Argentina. Further research is needed to determine the distribution of this virus in the country and its effects on raspberry plant production.